Scientific Atheism in East Germany (1963-1990): How to Turn a Hare into a Lion - Patzelt, Eva (Routledge Studies in Religion, 2024)
This book offers an in-depth, archive-based analysis of “scientific atheism”, focused on the development of the field in the German Democratic Republic (GDR). Scientific atheism was established as a Soviet import in 1963 at Jena University, with a presence in East German universities, propaganda and politics for nearly 30 years. The chapters explore the sociological work done by scientific atheists such as Olof Klohr, how they defined religion and atheism, and their role as actors of atheisation in various fields. As well as reflecting on the specific religious and political context in East Germany, the author makes comparison with other communist-ruled countries. Drawing on extensive and unique documentation, this book will be of interest to scholars of atheism and secularism, religion and politics, religious history, German history and East European studies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license